Städte und Gemeinden in sozialen Netzwerken. Motivation, Nutzen und Kosten. - (:unkn) unknown (My University, 2012)
Die Kommunen sind einerseits sehr an sozialen Netzwerken interessiert, um enger mit den Bürgerinnen und Bürgern in Kontakt zu kommen. Andererseits bestehen Unsicherheiten und viele offene Fragen. Diese Broschüre richtet sich an Interessierte, die sich ganz allgemein einen Überblick über soziale Netzwerke verschaffen wollen, vor der Entscheidung über das Engagement in sozialen Netzwerken stehen, oder wichtige Orientierungspunkte zum Einstieg in die Arbeit mit sozialen Netzwerken suchen. Die Autoren zeigen auf, welche Web 2.0-Techniken heute bestehen und warum sie so intensiv genutzt werden. Dabei wird stets der Blick auf die Frage gerichtet, in welcher Weise die sozialen Netzwerke für die Arbeit in Städten und Gemeinden relevant und nützlich sind.

Lively urban districts define themselves particularly through functioning social and institutional networks, which continually push forward the cohesion and exchange among tile citizens. In addition to neighbourhoods, mainly associations, citizens initiatives, local events and festivities are important elements of such a communitybuilding. In the course of the internet and Web 2.0 and the associated changes of the communication habits, digital neighbourhood platforms can constitute an additional element for this. In this context the issue is not only to replace the local free paper or the notices of associations, but also to create options for the establishment of new online communities in the neighbourhood. These can be general social networks, exchanges fora certain area of interest and many others. In the framework of the departmental research project "Innovations for urban neighbourhoods suitable for families and elderly persons" (2007-2009), different neighbourhood platforms were developed. The articlesummarises the most important findings from the research project on the planning, realisation and operation of neighbourhood platforms and considers these in the context of the problem of the "digital divide" as well as the current discussion about the significance of the private sphere in the "Social Web" On the part of the operators, sufficient technical knowledge, a secure legal basis, a target-oriented "market introduction" and an editorial staff unit which guarantees continuity and closeness to the neighbourhood must be permanently secured. As far as the interactive possibilities for participation are concerned, the participation of the users is still largely restricted to a group of persons with a "technology affinity" (generation problem). It is livelier if a vivid scene of associations and groups stands behind the online offer and uses this for itself as a platform.
Digital social networks in the city.
Keywords: Stadt; Gemeinde; Informationstechnologie; Kommunikationstechnologie; Kommunikation; Öffentlichkeit; Neue Medien; Internet; Web 2.0; Soziales Netzwerk